What Determines the Capital Structure of Listed Firms in Romania - Florinita Duca (CES Working Papers, 2012)
This paper examines the relative importance of four factors in the capital structure decisions of Romanian listed firms. The existing empirical research on capital structure has been largely confined to developed countries. The Romanian Financial Market has been developing at an exponential rate and dedicated research in the field is required. We used 100 firms listed in 2010 at the Bucharest Stock Exchange. The objective of this paper is to build on previous studies model all the important factors affecting capital structure decisions. We find that factors such as tangibility of assets, firm size, liquidity, and profitability have significant influences on the leverage structure chosen by firms. These results are believed to have significant implications for the theory of finance and to be of importance to the corporate treasure in choice of new financing and to the financial analyst.
Keywords: C10; G10; G30; 330; profitability; firm size; leverage; total assets turnover Romania